In Search of the Folk Society: Nationalism and Folklore Studies in Quebec - Handler, Richard (Culture)

(untitled) (Canadian Anthropology Society / Société Canadienne d’Anthropologie (CASCA), formerly/anciennement Canadian Ethnology Society / Société Canadienne d’Ethnologie, 1983)
Québécois nationalist ideologies base the uniqueness of Québécois identity on distinctive cultural traditions which, they urge, need to be protected. Among other cultural specialists, folklorists have worked to document traditional Québécois culture. But such research ‘objectifies’ traditional culture by placing it in new settings and attaching new meanings to it. And folklorists, as traditional in Québec as ‘tradition’ itself, thereby change the culture that they intended to preserve. Thus the question arises: was Québec ever a folk society, homogeneous and isolated, or were folk traditions continually recreated by scholars and nationalists alike?